2006
DOI: 10.1063/1.2335370
|View full text |Cite
|
Sign up to set email alerts
|

Probing of the electric field distribution in organic field effect transistor channel by microscopic second-harmonic generation

Abstract: Electric field distribution in channel of pentacene field effect transistor (FET) was successfully probed by microscopic optical second-harmonic generation (SHG) observation. Microspot SHG signals were acquired at various points in the channel with scanning a spot position along source-drain direction. For the FET at off state, enhanced SHG signal was observed, indicating the Laplace field formation reflecting the device geometry. This clearly supports the insulating nature of pentacene layer at off state. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 9 publications
3
65
0
1
Order By: Relevance
“…These phenomena are very similar to those observed in our previous EFI-SFG study of multi-layered OLEDs, and this behavior can be explained in terms of an electric field induced effect [9]. Thus, the SFG signal of ␣-NPD under the application of a forward voltage originates from the bulk of the ␣-NPD layer, as in the case of the EFI-SHG [24]. Note that no peaks derived from the ␣-NPD cation species are observed in the SFG spectra of the OLEDs due to the lack of the double-resonance effect, because the ␣-NPD cation species have no absorption around this wavelength.…”
Section: Resultssupporting
confidence: 73%
“…These phenomena are very similar to those observed in our previous EFI-SFG study of multi-layered OLEDs, and this behavior can be explained in terms of an electric field induced effect [9]. Thus, the SFG signal of ␣-NPD under the application of a forward voltage originates from the bulk of the ␣-NPD layer, as in the case of the EFI-SHG [24]. Note that no peaks derived from the ␣-NPD cation species are observed in the SFG spectra of the OLEDs due to the lack of the double-resonance effect, because the ␣-NPD cation species have no absorption around this wavelength.…”
Section: Resultssupporting
confidence: 73%
“…Second-harmonic-generation ͑SHG͒ microscopy is interface sensitive for materials with centrosymmetry 7 and has a better spatial resolution than IR microscopy. Manaka et al 8 have demonstrated that the SHG microscopy provides not only 2D mapping of electric field, but also carrier motion upon application of pulsed gate voltages. 9,10 In contrast to IR microscopy, however, this method does not provide any information of vibrational structure of molecules at the interfaces.…”
Section: Molecular Structure and Carrier Distributions At Semiconductmentioning
confidence: 99%
“…From Eqs. (3) and (4), it is clear that SH intensity distribution along the channel changes with change of the space charge field E s (x, t) [27][28][29], and thus with injected carrier distribution, ρ(x, t) (0b x b L). TRM-SHG measurement is based on this principle, and this approach allows nondestructive probing of a local electric field induced in materials because of the two-photon process, and also allows selective probing of a local electric field distribution in multi-layer systems in device applications such as OFET and organic electro-luminescent (EL) device by choosing laser wavelength appropriately.…”
Section: Probing Of Carrier Motion In Organic Materials As Dielectricmentioning
confidence: 98%